Intense and Small Freshwater Pools From Rainfall Investigated During Spurs‐2 on 9 November 2017 in the Eastern Tropical Pacific. Issue 2 (18th February 2020) - Reverdin, G.; Supply, A.; Drushka, K.; Thompson, E. J.; Asher, W. E.; Lourenço, A.
Abstract: During the second Salinity Processes in the Upper Ocean Regional Study (SPURS‐2) 2017 tropical Pacific cruise, two drifters were deployed on 9 November. The drifters measured temperature and salinity in the top 36 cm, wave spectra, and the noise of rain drops. During a short nearly circular survey with a 1.8‐km radius around the drifters, the R/V Revelle measured air‐sea fluxes, as well as temperature and salinity stratification in the top 1 m from a towed surface salinity profiler (SSP). A C‐band weather radar measuring rain rate within 1‐ to 100‐km range of the ship observed discrete rain cells organized in a system moving from the southeast to the northwest. Some of the intense rain cells were small scale (1 km in diameter or less) with short lifetimes yet dropped more than 5 cm of water in half an hour near the drifters, whereas the ship measured short rain episodes totaling 1.3 cm of rainfall mostly accompanied by very low wind. The data indicate a large spatial heterogeneity in temperature and salinity, with near‐surface freshening of up to 9 psu measured at different times by the two drifters (separated by less than 500 m) and by the SSP. The drifters indicate deepening of the fresh and cool surface layer during the rain which then thinned during the following 40 min with very low wind speed (<2 m/s). Patchy surface‐trapped cold and fresh layers were also observed by the SSP east of the drifters. The high spatial and temporal variability of rainfall and surface‐trapped fresh pools is discussed. Key Points: This event is the lowest sea surface salinity reported in the open ocean Patchy surface salinity was observed at 1‐km scale up to 1‐hr after rain Plain Language Summary: We present data illustrating remarkably low surface salinity for the open ocean, outside of the high latitudes near the sea ice or of river plumes. This event was observed by two instrumented drifters and a towed instrument during the R/V Revelle SPURS‐2 2017 cruise near 10°N/125°W on 9 November 2017. The large surface‐trapped fresh and cold signal was observed for up to an hour after the rain and was associated with low to very low surface wind. The data illustrate a large patchiness of the fresh and cold surface pool induced by intense but short‐lived rain events, at spatial scales of 1 km or less. Radar and ship meteorological data also illustrate a large spatial variability of the total rain accumulation, which in some places, such as near the drifters, exceeded 5 cm, whereas it was barely 1 cm, 1 km, or 2 km away. An estimate of the fresh layer thickness suggests that the fresh surface layer was up to 30 cm thick under the most intense rain but shallowed afterward to be on the order of 20 cm.